2007
DOI: 10.1128/mcb.01555-06
|View full text |Cite
|
Sign up to set email alerts
|

SCF E3-Mediated Autoubiquitination Negatively Regulates Activity of Cdc34 E2 but Plays a Nonessential Role in the Catalytic Cycle In Vitro and In Vivo

Abstract: One of the several still unexplained aspects of the mechanism by which the Cdc34/SCF RING-type ubiquitin ligases work is the marked stimulation of Cdc34 autoubiquitination, a phenomenon of unknown mechanism and significance. In in vitro experiments with single-lysine-containing Cdc34 mutant proteins of Saccharomyces cerevisiae, we found that the SCF-mediated stimulation of autoubiquitination is limited to specific N-terminal lysines modified via an intermolecular mechanism. In a striking contrast, SCF quenches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…Without SCF, Cdc34 is autoubiquitinated via intramolecular modification with no effect on enzyme function. However, when SCF is present, Cdc34 transfers ubiquitin to separate Cdc34 molecules via an intermolecular reaction, which inhibits their activity (12). We find that Ubc9 is incapable of either reaction and depends on E1 for sumoylation.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Without SCF, Cdc34 is autoubiquitinated via intramolecular modification with no effect on enzyme function. However, when SCF is present, Cdc34 transfers ubiquitin to separate Cdc34 molecules via an intermolecular reaction, which inhibits their activity (12). We find that Ubc9 is incapable of either reaction and depends on E1 for sumoylation.…”
Section: Discussionmentioning
confidence: 85%
“…Sumoylation of E1 at multiple lysines has previously been reported (6). To determine whether E1 is modified through intramolecular autosumoylation, similar to ubiquitin E1 and E2 (12), or whether it is dependent on transfer of SUMO from Ubc9, we performed in vitro sumoylation assays in the presence and absence of Ubc9 and with the catalytically inactive Ubc9-C93A (Fig. 2D).…”
Section: Figure 2 Cross-sumoylation Of E1 and Ubc9 Is Enhanced By Rhesmentioning
confidence: 86%
“…For example, Cdc34, an ubiquitin E2 enzyme, is autoubiquitinated in the presence of SCF (Skp1, Cdc53/Cull, and F-box protein), inhibiting its ubiquitin conjugating activity to transfer ubiquitin to separate Cdc34 molecules (49). Knipscheer et al (26) recently reported that mammalian Ubc9 autosumoylation regulates its target discrimination.…”
mentioning
confidence: 99%
“…There is evidence that RING E3s like Rad5 may play a more active role in ubiquitination than simply bringing the substrate into close proximity with the E2ϳUb. Several RING E3s have been shown to stimulate the synthesis of unanchored polyUb chains or autoubiquitination of their cognate E2s in the absence of substrates (22)(23)(24). This stimulation may be related to the ability of RING E3s to enhance reactivity of the E2ϳUb thiolester bond through allosteric effects (25,26).…”
mentioning
confidence: 99%